ALIH FUNGSI LAHAN SAWAH DI KABUPATEN LAMPUNG SELATAN - Pilatus Utama Mandala Putra; Raden Hanung Ismono; Maya Riantini (Lampung University, 2022)
Rice field conversion occurs due to the increasing land need. Rice fields were mostly converted to fulfill the needs of industry, regional development, and as residential land. The aims of this research were to know the rate of rice field conversion, factors that influence the rice field conversion, and the impact of the rice field conversion to the socioeconomic conditions of the community in South Lampung District. This research used a survey method and was conducted in three locations, namely: Natar, Jati Agung, and Tanjung Bintang Sub-districts. The first objective was analyzed by calculating the rate of partial land depreciation. The second objective was analyzed with logistic regression analysis.. The third objective was analyzed with qualitative and quantitative descriptive analysis. The results showed that the average rate of rice field conversion in South Lampung District is -0.02 percent per year. Factors that influence the rice field conversion were age, farming experience, and number of dependents. The impact caused by the rice field conversion were social mobility and decreased farmers' income by IDR 1,057,088.90 per month.Key words: conversion, land, rice fields